2018
DOI: 10.1002/jlb.3a0817-327rr
|View full text |Cite
|
Sign up to set email alerts
|

CIRP increases ICAM-1+ phenotype of neutrophils exhibiting elevated iNOS and NETs in sepsis

Abstract: Sepsis represents uncontrolled inflammation due to an infection. Cold-inducible RNA-binding protein (CIRP) is a stress-induced damage-associated molecular pattern (DAMP). A subset of neutrophils expressing ICAM-1 neutrophils was previously shown to produce high levels of reactive oxygen species. The role of CIRP for the development and function of ICAM-1 neutrophils during sepsis is unknown. We hypothesize that CIRP induces ICAM-1 expression in neutrophils causing injury to the lungs during sepsis. Using a mou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
115
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 86 publications
(122 citation statements)
references
References 50 publications
4
115
0
Order By: Relevance
“…In addition to homologues and orthologues, CIRP has at least two paralogues: RNA‐binding motif protein 3 (RBM3)—an RNA‐binding protein up‐regulated in response to low temperature and aggrecan promoter‐binding protein‐1 (APBP‐1)—a 19‐kDa DNA/RNA‐binding protein . CIRP is constitutively and ubiquitously expressed at low levels, with studies showing its presence in the brain, lungs, heart, liver, kidneys, and endometrium, as well as in macrophages and neutrophils . Recently, both CIRP expression and release have been shown to be induced in cellular stress and inflammatory conditions .…”
Section: Cirpmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition to homologues and orthologues, CIRP has at least two paralogues: RNA‐binding motif protein 3 (RBM3)—an RNA‐binding protein up‐regulated in response to low temperature and aggrecan promoter‐binding protein‐1 (APBP‐1)—a 19‐kDa DNA/RNA‐binding protein . CIRP is constitutively and ubiquitously expressed at low levels, with studies showing its presence in the brain, lungs, heart, liver, kidneys, and endometrium, as well as in macrophages and neutrophils . Recently, both CIRP expression and release have been shown to be induced in cellular stress and inflammatory conditions .…”
Section: Cirpmentioning
confidence: 99%
“…eCIRP promotes inflammation by binding to the TLR4‐MD2 receptor complex, leading to the activation and nuclear translocation of the transcription factor NF‐κB . Accordingly, CIRP −/− mice are protected and exhibit attenuated inflammation and organ injury in preclinical models of inflammatory diseases . These observations suggested that targeting eCIRP could be an effective therapeutic strategy for the treatment of inflammatory diseases.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Similar to other DAMPs, eCIRP recognizes Toll-like receptor 4 (TLR4) 5,8 expressed in macrophages, lymphocytes, and neutrophils to increase cytokine production 5 , T cell polarization 9 , and neutrophil activation 10 . Healthy mice injected with recombinant murine (rm) CIRP developed acute lung injury (ALI) via activation of macrophages, neutrophils, and endothelial cells, and displayed increased vascular permeability in the lungs 11,12 . Conversely, CIRP -/mice were protected from sepsis and ALI 5,6 .…”
Section: Introductionmentioning
confidence: 99%